Nuclear energy - an ethical use of resources - Alang Md Rashid, Nahrul Khair (2011)
Energy is the lifeblood of development. The energy use per capita in developed countries is higher than developing and much higher than less developd countries. Energy, however is finite in amount and can neither be created nor destroyed. It can only be converted from one form to another. This conversion changes the state of the resources and the change is generally is not reversible. Up to now, global development is being driven largely by fossil fuels – coal, oil, and gas together with renewabes such as hydro and geothermal. The use of renewable energy source such as solar, wind, and OTG are limited to non-industrial applications. Biofuel, derived from corn, palm oil, and jathropa for instance has yet to make impact in the energy equation. It has also raised an issue related to land use and competition with an equally important element of sustainability, which is food production. Further, biofuel does not in true sense renewables, rather it is ‘replenishable.’Fossil fuels are diminishing resources, they gradually become more costly to extract and process. Furthermore, the effect of large scale usage of coal to the environment has raised a lot of concerns. Another form of energy generation, generally termed as ‘alternative’ energy is the use of nuclear fission process. About 16% of global electricity production is currently generated by this means. Figure 2 shows the trend for electricity generation annually. However, it has caused great concerns in some segments of the public. Some of the concerns are real, others are due to misinformation. Recently, however, the situation has improved, due to the improved safety and the development of advanced type of nuclear power reactors. That situation has propelled nuclear energy to be seen as a viable source of energy for long term sustainability and energy security. Nuclear energy makes use of uranium, an element that has no other significant use besides energy production. On the contrary, fossil fuels, such as oil, has many other uses. The paper next argues that the use of nuclear energy is therefore as much an ethical choice that could overide other considerations, so often projected as the reasons for avoiding it. The next level is ethical use of nuclear energy itself. Technical as well as administrative procedures need to be in place for it to be used in ethical way.